Peningkatan Motivasi Belajar Peserta didik melalui Model Pembelajaran Kooperatif tipe Picture and Picture kelas 1 UPT SD Negeri 3 Pinrang - Isfianti Fadillah; Rahmawati Patta; Asma Asma (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2023)
Increasing the learning motivation of grade 1 students at UPT SD Negeri 3 Pinrang using the picture and picture learning model is the aim of the research carried out. This research uses the classroom action research method which is carried out in 2 cycles starting from the planning, implementation, observation to reflection stages, the data obtained from 27 students is then analyzed descriptively. The research results obtained in cycle I were in the category of sufficient student learning motivation with a percentage of 70.38%, then in cycle II it increased to the high category of 81.47%. So the use of the picture and picture learning model is stated to be able to increase the learning motivation of class 1 students.